Municipal Resource Allocation: Minimizing the Cost of Fire Protection - Seward, Samuel M.; Plane, Donald R.; Hendrick, Thomas E. (Management Science, 1978)
Municipal decision-makers face the difficult task of determining the amount of funds to be allocated for fire department services. This decision affects both the insurance class of the city and the total cost of fire protection. Total fire protection cost is the sum of the tax dollars spent for fire department services (public expenditures) and fire insurance premiums paid by residents and businesses (private expenditures). This paper presents an integer programming model to minimize the sum of these two costs. Since insurance costs reflect only property losses the model does not explicitly include the consequences of loss of life or injury. Since the protection of persons is an important part of the fire protection mission it is important to realize that the model produces a lower bound for the value and level of fire department services. We go on to show how the results can be used to provide a method of inputing a life hazard benefit for decisions which produce more fire protection than suggested by the cost-minimizing model. The model was applied in Boulder, Colorado; the ways in which the results may be incorporated into the political decision process are also described.